Physiological deterioration prior to in-hospital cardiac arrest: What does the National Early Warning Score-2 miss? - Sherif Gonem; Daniella Draicchio; Ayad Mohamed; Sally Wood; Kelly Shiel; Steve Briggs; Tricia M McKeever; Dominick Shaw (Resuscitation Plus)
Aim: To determine the frequency with which the National Early Warning Score-2 (NEWS-2) fails to detect physiological deterioration preceding in-hospital cardiac arrest (IHCA). Methods: We conducted a retrospective observational study of all adult patients (age ≥ 18) who had suffered an IHCA between 1st July 2019 and 31st December 2021 in two large acute hospitals located in an urban centre (Nottingham, UK). Clinical observations and case notes were examined for the period leading up to IHCA events to determine if there was evidence of physiological deterioration which warranted an urgent patient assessment, whether NEWS-2 was triggered, and whether an urgent assessment actually took place. Results: Urgent assessment was indicated in the lead-up to 126/374 (33.7 %) IHCA cases, and NEWS-2 failed to trigger in 20 of these cases (15.9 %). An urgent assessment took place in 89/106 (84.0 %) cases where NEWS-2 was triggered, and 13/20 (65.0 %) cases where NEWS-2 was not triggered, with the difference in proportions being statistically significant (p = 0.048). Half of cases in which NEWS-2 missed a physiological deterioration were related to a new or rising oxygen requirement. Conclusions: A significant proportion of IHCA events are preceded by clinically important abnormalities in vital signs which are not detected by NEWS-2. This may be a causative factor in some failure-to-rescue events.